Sistem Penggajian Berbasis Web untuk Butik Busana Fashion: Implementasi Metode RAD - Siti Rokhaila; Ana Kurniawati; Dina Agusten (G-Tech: Jurnal Teknologi Terapan, 2024)
Employee salary management is becoming an important aspect in the fashion industry. The current payroll system in Fashion Boutique still uses slow and inefficient manual calculations. Therefore, a website was created to manage employee payroll. This study aims to optimize salary management through a web-based Rapid Application Development (RAD) approach. The RAD method was chosen because it is responsive to rapid business changes. By conducting needs analysis, design, implementation, and testing, an efficient payroll management system integrated with web access was successfully developed. Trials are conducted with black box testing, device testing, desktop browser, and end user. Payroll websites have proven to match user expectations, working well across multiple devices and browsers. The results of this study contribute to improving operational efficiency and accuracy of employee salary management in the context of a dynamic fashion industry, especially in Fashion Fashion Boutiques.